دور مواقع التواصل الاجتماعي في تشكيل الوعي السياسي لدى المستخدم الجزائري-الفيسبوك دراسة ميدانية بجامعة عبد الحميد بن باديس خروبة مستغانم - بلقاسمي, مسعود (كلية العلوم الاجتماعية, 2021)
Abstract This study amis to recognition the formation of the politicalsense by face book site with the collegestudent and whichisseeking to discover the attention ofthe collegestudent on differentpolitical case, also to know the importance of the face book in getting the political science which leads to conformation the political opinion and this last contributes the politicalsense thisstudywasdone on student of political science as a communitysearch and thisstudyconsiderwith the descriptive searches and weaccredit in ourstudy on theconcert protocolwithstudy 32% from the vocabulaire of the search societyaccredited to the form of the questionnaire as a means to collect the liststhoseare formative from 4 parts ; 1- Personalliststhen the attention of the universalstudentwith the politicalcases . 2- Employment of the collegestudents face book site in collecting the poltical science. 3- Using face book as a range to conformation the political opinion. 4- Lastly the parcticalside of the studystartingfromshowing the rosters analyzethem and explainthemuntilaccess to results for the study and a final.
Keywords: مواقع التواصل الاجتماعي-الوعي السياسي-الفيسبوك